The importance of melatonin in the regulation of metabolism, eating behavior, sleep, and the prospects for the use of melatonin drugs for obesity treatment - E. S. Tsvetkova; T. I. Romantsova; M. G. Poluektov; G. E. Runova; I. V. Glinkina; V. V. Fadeev (Ожирение и метаболизм, 2021)
Melatonin is a special hormone that act as an internal synchronizer of circadian rhythms, the organism physiology and behavior to the environmental day and night and seasons of the year. The present urban society and the industrial production processes as organized should be considered, as both depend on the presence of indoor lights during the night and include the profuse use of electronic devices whose screens are rich in blue wavelength light. Light during the night delays the beginning of the secretory episode of melatonin and blunts its peak, causing chronic hypomelatoninemia. Hypomelatonemia, that causes deprivation of sleep and eating behavior disorders, along with low physical activity, can be the reason of the obesity, «non-infectious epidemic of the 21st century». According to this, the use of melatonin drugs for obesity treatment can be effective. Further prospective, controlled, randomized trials in this area are required to confirm this hypothesis.